PENGARUH PROMOSI, KUALITAS PELAYANAN TERHADAP NIAT DATANG KEMBALI: KEPUASAN PELANGGAN HOTEL BINTANG EMPAT - Sulandra, I Ketut; Surata, I Ketut; H. Sihombing, Irene Hanna (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2024)
This research aims to identify the influence of promotions and service quality on customers' intentions to return to four-star hotels in the Mumbul Region, Nusa Dua, as well as the role of customer satisfaction as a mediator in this relationship. The type of research used in this research is quantitative. The subjects (respondents) of this research were guests who had enjoyed the facilities or services at a four-star hotel in the Mumbul area, Nusa Dua. The research sample consisted of 166 visitors with data collection techniques carried out using a questionnaire (questionnaire) with a Likert scale which had been tested for validity and reliability. Data from this research were processed using descriptive analysis techniques and SEM PLS. The results of this research show that promotion has no significant effect on intention to return, service quality has a significant effect on intention to return, but promotion has a significant effect on customer satisfaction. Service quality has a significant effect on customer satisfaction, and customer satisfaction has a significant effect on intention to return. Customer satisfaction partially mediates the influence of promotions on intention to return with a VAF value of 67%, and customer satisfaction partially mediates the influence of service quality on intention to return with a VAF value of 67.6%. By understanding the indications of these findings, hotel management can direct their efforts to improve service quality, strengthen effective promotions, and ensure high levels of customer satisfaction to build loyalty and increase guest retention rates in the future.